Parvana’s Trilogy: A Study of Violence toward Afghanistan Women and Girls - Agustina, Hiqma Nur; Ramalia, Tenia (PALASTREN: Jurnal Studi Gender, 2017)
Afghan women and girls became the portray of the victim of violence in the last years until the recent years. The issue of violence toward Afghan women and girls often arise and being the debate in the international public. The news about the tragedy spread through the newspaper, printed and online, and also in the literature world. The exposure of their sufferings as the impact of war, conflict among the ethnics, Talizam rezim reflected in the Parvana's Trilogy named The Breadwinner (2000), Parvana's Journey (2002), and Mud City (2003). These trilogy were wriiten by Deborah Ellis. How the women and girls became the most victim which received violence caused by all of the trigger displayed obviously show the social facts of violence and the structure of violence toward happened to them. Those will be discussed in this paper to get the deep comprehension about the woman and girls' impact after they get the violence. The theory of violence and framing analysis will be used to analyze in order to get the result of the cause by the viooence and abuse itself. The outcome of the study shows that many efforts done by women and girls to overcome their difficult lives, such as pretending being boys, human trafficking, and living as refugees are the ways to survive from the worst violence caused by the war, conflict between ethnics and Taliban rezime.